1978
DOI: 10.4039/ent110623-6
|View full text |Cite
|
Sign up to set email alerts
|

EFFECT OF CONSTANT TEMPERATURES ON THE NUMBER OF LARVAL INSTARS OF THE ORIENTAL FRUIT MOTH, GRAPHOLITHA MOLESTA (LEPIDOPTERA: TORTRICIDAE)

Abstract: Laboratory tests, at constant temperatures, were conducted to evaluate quantitatively the influence of temperature on development of the Oriental fruit moth, Grapholitha molesta (Busck). The results showed that at the highest temperature (30°C) some larvae had four instars and some had five, indicating a mixed population. Fifth instar larvae developed only at the highest temperature (30°C) where larval development was also most rapid. It can, therefore, be assumed that the Oriental fruit moth has four distinct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

1980
1980
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 3 publications
(4 reference statements)
1
8
0
Order By: Relevance
“…308C) was favourable for increasing the number of instars of N. huttoni. Similar results were reported in Platynota stultana (Walsingham) (Lepidoptera: Tortricidae) (ZennerPolania & Helgesen 1973), Enallagma hageni Walsh and E. aspersum (Hagen) (Odonata) (Ingram & Jenner 1976), Grapholitha molesta (Busck) (Lepidoptera: Tortricidae) (Roberts et al 1978), Argia vivida Hagen (Zygoptera: Coenagrionidae) (Leggott & Pritchard 1985) and Quadricalcarifera puncutatella (Motschulsky) (Lepidoptera: Notodontidae) (Kamata & Igarashi 1995). However, the opposite effect, with lower temperatures increasing the number of instars, was also reported (Tanaka 1979;Nagasawa 1988;Allen & Keller 1991;Kingsolver 2007).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…308C) was favourable for increasing the number of instars of N. huttoni. Similar results were reported in Platynota stultana (Walsingham) (Lepidoptera: Tortricidae) (ZennerPolania & Helgesen 1973), Enallagma hageni Walsh and E. aspersum (Hagen) (Odonata) (Ingram & Jenner 1976), Grapholitha molesta (Busck) (Lepidoptera: Tortricidae) (Roberts et al 1978), Argia vivida Hagen (Zygoptera: Coenagrionidae) (Leggott & Pritchard 1985) and Quadricalcarifera puncutatella (Motschulsky) (Lepidoptera: Notodontidae) (Kamata & Igarashi 1995). However, the opposite effect, with lower temperatures increasing the number of instars, was also reported (Tanaka 1979;Nagasawa 1988;Allen & Keller 1991;Kingsolver 2007).…”
Section: Discussionsupporting
confidence: 83%
“…The number of instars, however, varies intraspecifically in a considerable number of species. Variation in number of instars has been reported to be related to factors such as sex (Fleischmann et al 1968;Penz 1990;Garcia-Barros 2006;Esperk et al 2007b), temperature (Roberts et al 1978;Tanaka 1979;Kamata & Igarashi 1995;Zhu & Tanaka 2004;Kingsolver 2007), humidity (Elder 1989), photoperiod (Ingram & Jenner 1976;Tanaka 1979;Tanaka et al 1999;Taniguchi & Tomioka 2003;Zhu & Tanaka 2004), crowding (Long 1953;Leonard 1968), host plants or food quality and quantity (Penz 1990;Casimero et al 2000;Bentancourt et al 2004;Azidah & Sofian-Azirum 2006) and heredity (Brehme 1939;Solonon 1973;Zhou & Topp 2000) in many insects.…”
Section: Introductionmentioning
confidence: 99%
“…This difference could depend on different food sources or quality, because L. botrana adult weight was higher when larvae had been reared on unripe berries than on ßoral clusters before ßow-ering (Torres-Vila 1996). Also, the temperature (much higher in summer than in spring) could be a factor inßuencing the larval size, as previously reported for Cydia molesta (Busck) (Roberts et al 1978), even though laboratory data on L. botrana showed that larval size is greater at lower temperatures (Sáenz-de-Cabezó n Irigaray et al 2006).…”
Section: Discussionmentioning
confidence: 60%
“…2). The presence of pink body colour has been experimentally verified as a reliable indicator of the final instar (4th or 5th) but is not seen in the instar at an early stage (Russell, 1986 Chaudhry (1956) (24 °C), but was not evident in the head capsule width data of Roberts et al (1978).…”
Section: Influence Of Diapausementioning
confidence: 99%
“…The Oriental fruit moth (OFM) (Grapholita molesta (Busck) The number of larval instars is widely reported as 5 (Reichart & Bodor, 1972) or as 4 or 5 (Peterson & Haeussler, 1928;Besson & Joly, 1976, Roberts et al, 1978, Yokoyama et al, 1987. These authors provide means and/or ranges for the larval head capsule widths of the various instars and both Besson & Joly (1976) and Reichart & Bodor (1972) describe head capsule and body colour for all instars.…”
Section: Introductionmentioning
confidence: 99%